EMBEDDING IDENTIFICATION DATA WITHIN IMAGES BASED ON SINUSOIDAL GRATINGS FOR MOBILE APPLICATIONS - A. A. Bоriskevich (Informatika)
A method of optically visualized block watermarking the images based on the proposed models of embedded message, marked image and robust textural correlation message extracting is developed. The results of computer modeling are presented.